Thermodynamic study of carbon nanotube production from greenhouse gases during syngas synthesis - Maphutha, Selby Kwena (My University, 2010)
Global warming has become a major topic for the public in recent years and many institutions and industries have been pushed to find a ‘cure’ for it. The most wildly known culprit for global warming is carbon dioxide and several methods for the treatment of this gas have been proposed. There is thermal decomposition, capturing methods and chemical decomposition. This study looks at the conversion of carbon dioxide and another greenhouse gas, methane, into carbon nanotubes and syngas (hydrogen and carbon monoxide), which is a precursor to the petroleum compounds in the Fischer-Tropsch process. The study was done experimentally by running a CO2\CH4 mixture through a CVD reactor, at temperatures ranging from 650 to 950oC, and two catalysts (a lanthanum-nickel alloy and a mischmetalnickel alloy separately). Theoretically, the thermodynamics of this process were done at temperatures ranging from 600 to 1500 K. The products from the experiment were analysed using a Transmission electron microscope (both normal and high resolution), Raman spectroscopy and Gas chromatography. Using the proposed catalysts, the carbon dioxide and the methane were decomposed, forming carbon nanofibers and carbon nanotubes as shown by the transmission electron microscope images. The carbon nanofibers and nanotubes became less defined and generally fewer in number as the temperature increased. The thermodynamics also showed that the carbon decreased and the syngas increased as the temperature increased. The Gas chromatography showed that there was syngas that was produced during the experimental process. The mischmetal-nickel alloy proved to convert more of the greenhouse gasses into syngas than the lanthanum-nickel alloy.